2005
DOI: 10.2113/35.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Intertidal Mangrove Foraminifera From the Central Great Barrier Reef Shelf, Australia: Implications for Sea-Level Reconstruction

Abstract: Contemporary foraminiferal samples and environmental information were collected from three fringing mangrove environments (Sandfly Creek Transect 1 and 2, and Cocoa Creek) in Cleveland Bay, and an estuarine mangrove environment (Saunders Creek) in Halifax Bay, on the central Great Barrier Reef (GBR) coastline, Australia, to elucidate the relationship of the foraminiferal assemblages with the environment. The data support the vertical zonation concept, which suggests that the distribution of foraminifera in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 48 publications
1
50
0
5
Order By: Relevance
“…Work by Horton et al (2005a) and Debenay et al (2004) have shown that Foraminifera are capable of reconstructing sea level in tropical environments, however the fossil record is prone to preservation issues with Debenay et al (2004) stating that foraminifera in mangrove environments are "dramatically affected by taphonomic processes". Woodroffe et al (2005) in Australia also demonstrate that foraminifera preservation within mangrove sediments is problematic. Diatom preservation is also problematic within fossil cores, potentially due to the high salinity and temperature of the mangrove environments that promotes their dissolution (Barker et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Work by Horton et al (2005a) and Debenay et al (2004) have shown that Foraminifera are capable of reconstructing sea level in tropical environments, however the fossil record is prone to preservation issues with Debenay et al (2004) stating that foraminifera in mangrove environments are "dramatically affected by taphonomic processes". Woodroffe et al (2005) in Australia also demonstrate that foraminifera preservation within mangrove sediments is problematic. Diatom preservation is also problematic within fossil cores, potentially due to the high salinity and temperature of the mangrove environments that promotes their dissolution (Barker et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Great Barrier Reef on the northeast coast is a tectonically stable area, and the focus of many sealevel studies (Chappell, 1983;Lambeck and Nakada, 1990;Nakada and Lambeck, 1989;Woodroffe et al, 2005). Studies indicate sea level reached modern height by 7,000 cal.…”
Section: Holocene Records From the Atherton Tablelandsmentioning
confidence: 99%
“…Tradicionalmente la mayoría de las investigaciones consideran solo el centímetro superior del sedimento para estudios foraminiferológicos (e.g., Debenay et al 1998, Alve & Murray 1999, Horton et al 1999, Murray & Alve 1999, Gehrels et al 2001, Horton et al 2003, Edwards et al 2004, Horton et al 2005, Woodroffe et al 2005. Esto puede provocar que las especies que Fig.…”
Section: Métodosunclassified
“…Un gran número de trabajos han estudiado la distribución de los foraminíferos modernos en las marismas salobres del Atlántico Norte (e.g., Le Campion 1970, Phleger 1970, Pujos 1976, Scott & Medioli 1978, 1980a, Smith et al 1984, Murray 1991, Gehrels 1994a, 1994b, De Rijk 1995, De Rijk & Troelstra 1997, Cearreta et al 2002, Moreno et al 2005, Woodroffe et al 2005, Horton & Edwards 2006, Fatela et al 2007, Horton & Edwards 2006, Horton & Murray 2007, Horton & Culver 2008, Leorri et al 2008, del Atlántico Sur (e.g., Cusminski et al 2009) y del Pacífico Norte (e.g., Williams 1989, Patterson 1990, Jennings & Nelson 1992, Guilbault et al 1995, 1996, Scott et al 1996, lo que en algunos casos ha permitido la posterior aplicación de la "función de transferencia".…”
unclassified
See 1 more Smart Citation